Management of Revenues Collection of Thasala Local Administrative Organization, Munjakiri District, Khonkaen Province - ช่างทา อนุวัตร (Journal of Graduate MCU KhonKaen Campus, 2015)
This research had the objective to study the problems of administering revenue collection, and to provide recommendations for guidelines to improve revenue collection by the Tha Sala Tambon Administrative Organization (TAO) in Manjakiri District of Khon Kaen Province. Data were collected from 28 staff of the TAO using questionnaires and observation. This study found that the TAO faces problems of inadequate revenue collection staff, poor coordination, shortage of equipment to aid tax collection, out-of-date information on tax payments, insufficient public relations about paying taxes, limited channels for paying taxes, and lack of involvement of community leaders and eligible taxpayers. The management of revenue collection under the legal structure of the TAO generates only a small amount of revenue when compared with the central government receipts and subsides to the TAO. Thus, there is little motivation of the TAO to conduct tax collection by itself; it is easier to rely on the central government support. Based on the findings of this study, it is recommended that there should be more use of tax mapping and assets registration tools to increase efficiency of revenue collection. There should be more outreach to eligible taxpayers to make it more convenient to pay taxes, and provide after hours tax collection services. There should be awards and prizes for prompt taxpayers and more publicity of the taxes collected so that the community is aware and informed on a regular basis.